2021
DOI: 10.1177/0300060520983263
|View full text |Cite
|
Sign up to set email alerts
|

Physiologic and hemodynamic changes in patients undergoing open abdominal cytoreductive surgery with hyperthermic intraperitoneal chemotherapy

Abstract: Objective We aimed to determine the physiological and hemodynamic changes in patients who were undergoing hyperthermic intraperitoneal chemotherapy (HIPEC) cytoreductive surgeries. Methods This prospective, observational study enrolled 21 patients who were undergoing elective cytoreductive surgery with HIPEC at our hospital over 2 years. We collected vital signs, hemodynamic parameters including global end-diastolic volume index (GEVI) and extravascular lung water index (ELWI) using the VolumeView™ system, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 51 publications
0
18
0
Order By: Relevance
“…Fifteen studies with a total of 1,445 patients were included in the qualitative synthesis presented in ►Table 1. 15,24,[35][36][37][38][39][40][41][42][43][44][45][46][47]…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fifteen studies with a total of 1,445 patients were included in the qualitative synthesis presented in ►Table 1. 15,24,[35][36][37][38][39][40][41][42][43][44][45][46][47]…”
Section: Resultsmentioning
confidence: 99%
“…15,24,[35][36][37][38][39][40][41][42][43][44][45][46][47] Out of 15 studies, 13 studies reported primary tumor location (93%). 15,24,[35][36][37][38][39][40][41][42][43][44][45][46] Neoadjuvant chemotherapy was administered in two studies. 7,24…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are a lot of hemodynamic changes during HIPEC due to increased temperature, such as increased heart rate, increased CI , increased oxygen consumption and decreased systemic vascular resistance [ 24 ]. Bleeding results in hypovolemia, as well as the major surgical resections, physicochemical trauma and HIPEC by altering the capillary permeability [ 2 , 24 ]. While optimal fluid therapy often necessitates aggressive fluid resuscitation, avoiding fluid overdose is important [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…A continuous infusion of a vasopressor, phenylephrine or norepinephrine, was administered to maintain the mean arterial pressure (MAP) and HR within 20% of the basal preoperative value. Hydroxyethyl starch (6% 130/0.4) in a balanced electrolyte solution (Volulyte ® , Fresenius Kabi AG, Bad Homburg, Germany) was used for perioperative fluid management accompanied by crystalloid infusion [ 19 ]. The body temperature was monitored continuously using an esophageal probe, and a Bair Hugger™ upper body airstream blanket (3M Deutschland GmbH, Neuss, Germany) with a forced-air warmer, hot IV line, and heated circuit was applied for warming during the CRS phase.…”
Section: Methodsmentioning
confidence: 99%